Modified ferric sodium pyrophosphate as well as preparation method and application thereof
By introducing a mixed valence state of Fe3+ and Fe2+ in sodium ferric phosphate, and improving sodium ion diffusion through the coating layer, the problem of insufficient conductivity and diffusion ability is solved, and its performance in sodium ion batteries is significantly improved .
Patent Information
- Application Number
- CN202411888373.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-20
AI Technical Summary
In the prior art, the electron conductivity and ion diffusion ability of sodium ferric phosphate pyrophosphate have poor electron conductivity and ion diffusion ability, resulting in poor electrochemical performance in sodium ion batteries.
By mixing Na4Fe3(PO4)2P2O7 with a specific content and type of phosphorus source and sodium supplement agent, a mixed valence state of Fe3+ and Fe2+ is formed, and the sodium ion diffusion efficiency is improved through the coating layer.
It significantly improves the electronic conductivity and sodium ion diffusion performance of sodium ferric phosphate, and improves its specific capacity, rate performance and cycling performance in sodium ion batteries.
Smart Images

Figure CN119409160A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery positive electrode materials, and in particular, relates to modified sodium iron pyrophosphate and a preparation method and application thereof. Background Art
[0002] At present, sodium-ion batteries have gradually developed into an important electrochemical energy storage and power source. The most representative of this type of battery is the sodium secondary battery (SIBs), which generates electrical energy due to the change in chemical potential when sodium ions in the positive and negative electrodes are embedded and deintercalated.
[0003] The cathode material has a direct and dominant role in the performance of SIBs, so many researchers are committed to developing cathode materials with large capacity, fast charge / discharge speed, long cycle life, and reversible sodium ion embedding and de-embedding. Sodium pyrophosphate iron phosphate Na4Fe3(PO4)2P2O7 material has very good environmental friendliness and abundant resources, but its electronic conductivity and ion diffusion capacity are poor, resulting in unsatisfactory electrochemical performance of the material. The current conventional modification method is to coat the surface of sodium pyrophosphate iron phosphate with conductive material (carbon).
[0004] Although the conductivity of the surface of Na4Fe3(PO4)2P2O7 material is enhanced by carbon coating in the prior art, this carbon coating modification method has little effect on the conductivity of the material itself. Therefore, there is an urgent need for a method to enhance the conductivity and ion diffusion performance of sodium iron pyrophosphate, thereby improving the rate performance and cycle performance of the material, which is of great significance to the research and development of sodium ion batteries. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides a modified sodium ferric pyrophosphate and a preparation method and application thereof.
[0006] In the first aspect, an embodiment of the present invention proposes a modified sodium ferric pyrophosphate, comprising a core and a coating layer coated on the surface of the core; wherein the core is Na4Fe3(PO4)2P2O7, and the coating layer comprises a sodium supplement and a reaction product generated by a high-temperature reaction of the sodium supplement and a phosphorus source.
[0007] In some embodiments, the molar ratio of the sodium supplement to the Na4Fe3(PO4)2P2O7 is denoted as a, and the molar ratio of the phosphorus source to the Na4Fe3(PO4)2P2O7 is denoted as b, then 1<c=(10a) 2 / (2.25b)<5.33, and 0.015<a<0.06, 0.01<b<0.03.
[0008] In some embodiments, the sodium supplement is sodium oxalate.
[0009] In some embodiments, the phosphorus source includes at least one of phosphoric acid, diammonium phosphate, and monoammonium phosphate.
[0010] In a second aspect, an embodiment of the present invention further provides a method for preparing the modified sodium ferric pyrophosphate as described in the first aspect, comprising the following steps:
[0011] (1) mixing Na4Fe3(PO4)2P2O7, a sodium supplement and a phosphorus source to obtain a mixture;
[0012] (2) The mixture is sintered at high temperature, and then ground to obtain the modified sodium ferric pyrophosphate.
[0013] In some embodiments, in step (1), the particle size of the mixture is 2 to 15 μm.
[0014] In some embodiments, in step (2), the high temperature sintering is performed under the protection of an inert gas, and the inert gas includes at least one of nitrogen and argon;
[0015] And / or, the sintering temperature of the high temperature sintering is 700-800° C., and the sintering time is 9-12 hours.
[0016] In some embodiments, in the step (2), the D50 particle size of the modified sodium ferric pyrophosphate obtained after grinding is 0.5 to 8 μm.
[0017] In a third aspect, an embodiment of the present invention further proposes an application of the modified sodium ferric pyrophosphate as described in the first aspect or the modified sodium ferric pyrophosphate prepared by the preparation method described in the second aspect in a sodium ion battery, wherein the modified sodium ferric pyrophosphate is used as the positive electrode active material of the sodium ion battery.
[0018] In some embodiments, the sodium ion battery further comprises a negative electrode and an electrolyte; the negative electrode is a sodium metal sheet, and the electrolyte comprises sodium hexafluorophosphate, ethylene carbonate and dimethyl carbonate.
[0019] The advantages and beneficial effects of the embodiments of the present invention are as follows:
[0020] In the embodiment of the present invention, Na4Fe3(PO4)2P2O7 is mixed with a phosphorus source of a specific content and type and calcined to cause Na and Fe defects in Na4Fe3(PO4)2P2O7 and form Fe 3+ and Fe 2+mixed valence state, thereby greatly improving the electronic conductivity of Na4Fe3(PO4)2P2O7; and at the same time, by adding a specific amount of sodium supplement, the capacity decay caused by sodium loss can be compensated, and part of the product generated by the reaction of the sodium supplement with the phosphorus source will be coated on the surface of the Na4Fe3(PO4)2P2O7 material, which can improve the sodium ion diffusion efficiency of the Na4Fe3(PO4)2P2O7 material, thereby making the prepared modified sodium iron pyrophosphate have a higher specific capacity and excellent rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the first charge and discharge curve of the modified sodium iron pyrophosphate prepared in Example 1 of the present invention at 0.1C. DETAILED DESCRIPTION
[0022] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0023] Where values are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.
[0024] Herein, the words "comprises" and "includes" and variations thereof mean that other elements or integers which are permitted but not specifically described may be included.
[0025] In this article, the term "and / or" is merely a term used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0026] In the first aspect, an embodiment of the present invention proposes a modified sodium ferric pyrophosphate, comprising a core and a coating layer coated on the surface of the core; wherein the core is Na4Fe3(PO4)2P2O7, and the coating layer comprises a sodium supplement and a reaction product generated by a high-temperature reaction of the sodium supplement and a phosphorus source.
[0027] The modified sodium ferric pyrophosphate in the embodiment of the present invention has a core-shell structure, wherein the core is Na4Fe3(PO4)2P2O7, and the coating layer is a composite material composed of a sodium supplement and a reaction product generated by a high-temperature reaction of the sodium supplement and a phosphorus source, wherein the sodium supplement can make up for the capacity attenuation caused by sodium loss, and the coating layer can improve the sodium ion diffusion efficiency of Na4Fe3(PO4)2P2O7, thereby making the prepared modified sodium ferric pyrophosphate have a higher specific capacity and excellent rate performance and cycle performance, and has broad research prospects and application value.
[0028] In some embodiments, the molar ratio of the sodium supplement to the Na4Fe3(PO4)2P2O7 is denoted as a, and the molar ratio of the phosphorus source to the Na4Fe3(PO4)2P2O7 is denoted as b, then 1<c=(10a) 2 / (2.25b)<5.33, and 0.015<a<0.06, 0.01<b<0.03. It should be noted that the value ranges of a, b, and c do not include the endpoint values of their intervals.
[0029] In some embodiments, the sodium supplement is sodium oxalate (Na2C2O4), which does not contain precious metals and has a low cost.
[0030] In some embodiments, the phosphorus source includes at least one of phosphoric acid, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate. The selected phosphorus source has a wide range of raw material sources, low cost, and few impurities.
[0031] In a second aspect, an embodiment of the present invention further provides a method for preparing the modified sodium ferric pyrophosphate as described in the first aspect, comprising the following steps:
[0032] (1) mixing Na4Fe3(PO4)2P2O7, a sodium supplement and a phosphorus source to obtain a mixture;
[0033] (2) The mixture is sintered at high temperature, and then ground to obtain the modified sodium ferric pyrophosphate.
[0034] The embodiment of the present invention can effectively compensate for the capacity decay caused by sodium loss by mixing Na4Fe3(PO4)2P2O7 with a phosphorus source and a sodium supplement and calcining them, and can also improve the sodium ion diffusion efficiency of Na4Fe3(PO4)2P2O7, so that the prepared modified sodium iron pyrophosphate has a higher specific capacity and excellent rate performance and cycle performance; and the preparation method of the modified sodium iron pyrophosphate has a simple preparation process, is easy to operate, has low cost, is suitable for industrial large-scale production, and is of great significance to the research and development of sodium ion batteries.
[0035] In some embodiments, in step (1), the particle size of the mixture is 2 to 15 μm, non-limiting examples include 2 μm, 4 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, etc.
[0036] In some embodiments, in step (2), the high temperature sintering is performed under the protection of an inert gas, and the inert gas includes at least one of nitrogen and argon;
[0037] And / or, the sintering temperature of the high temperature sintering is 700-800°C (non-limiting examples include: 700°C, 750°C, 780°C, 800°C, etc.), and the sintering time is 9-12h (non-limiting examples include: 9h, 10h, 11h, 12h, etc.). By controlling the sintering temperature within the range of 700-800°C, it is more conducive to the sodium supplement and the phosphorus source to react to form a coating layer, and at the same time, the phosphorus source can effectively adjust the mixed valence state of Fe in Na4Fe3(PO4)2P2O7, thereby improving the rate performance and cycle performance of the material; if the sintering temperature is too low, the sodium supplement and the phosphorus source are difficult to enter Na4Fe3(PO4)2P2O7, which will result in poor cycle stability of the obtained material; but if the sintering temperature is too high, the material particles will be severely bonded, thereby causing its electrochemical performance to decrease.
[0038] In some embodiments, in step (2), the D50 particle size of the modified sodium ferric pyrophosphate obtained after grinding is 0.5 to 8 μm, non-limiting examples include: 0.5 μm, 1 μm, 2 μm, 4 μm, 5 μm, 6 μm, 8 μm, etc.
[0039] In a third aspect, an embodiment of the present invention further proposes an application of the modified sodium ferric pyrophosphate as described in the first aspect or the modified sodium ferric pyrophosphate prepared by the preparation method described in the second aspect in a sodium ion battery, wherein the modified sodium ferric pyrophosphate is used as the positive electrode active material of the sodium ion battery.
[0040] In some embodiments, the sodium ion battery further comprises a negative electrode and an electrolyte; the negative electrode is a sodium metal sheet, and the electrolyte comprises sodium hexafluorophosphate (NaPF6), ethylene carbonate (EC) and dimethyl carbonate (DMC).
[0041] The following are non-limiting examples and comparative examples of the present invention. It should be noted that the schemes of the comparative examples are not prior art and are only provided for comparison with the schemes of the embodiments and are not intended to limit the present invention. Unless otherwise specified, the various raw materials used in the embodiments and comparative examples are conventional commercial products or can be prepared by known methods.
[0042] Example 1
[0043] This embodiment provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0044] (1) Na4Fe3(PO4)2P2O7, Na2C2O4 and phosphoric acid were mixed by dry stirring at a molar ratio of 1:0.035:0.02 to obtain a mixture with a particle size of 8 μm;
[0045] (2) The mixture obtained in step (1) is sintered at 750° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0046] In this embodiment, the molar ratio of the sodium supplement Na2C2O4 to Na4Fe3(PO4)2P2O7 is a=0.035, and the molar ratio of the phosphorus source to Na4Fe3(PO4)2P2O7 is b=0.02, then c=(10a) 2 / (2.25b)=2.72.
[0047] The modified sodium iron pyrophosphate prepared in this embodiment includes a Na4Fe3(PO4)2P2O7 core and a coating layer coated on the surface thereof, wherein the coating layer includes sodium phosphate and Na2C2O4, and the Na4Fe3(PO4)2P2O7 core contains defects of Na and Fe, forming Fe 3+ and Fe 2+ of mixed valence.
[0048] Figure 1 This is the first charge and discharge curve of the modified sodium ferric pyrophosphate prepared in this embodiment at 0.1C. It can be seen from the figure that the modified sodium ferric pyrophosphate prepared in this embodiment has high first coulombic efficiency, large charge and discharge capacity, and excellent electrochemical performance.
[0049] Example 2
[0050] This embodiment provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0051] (1) Na4Fe3(PO4)2P2O7, Na2C2O4 and phosphoric acid were mixed by dry stirring at a molar ratio of 1:0.03:0.02 to obtain a mixture with a particle size of 8 μm;
[0052] (2) The mixture obtained in step (1) is sintered at 750° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0053] In this embodiment, the molar ratio of the sodium supplement Na2C2O4 to Na4Fe3(PO4)2P2O7 is a=0.03, and the molar ratio of the phosphorus source to Na4Fe3(PO4)2P2O7 is b=0.02, then c=(10a) 2 / (2.25b)=2.
[0054] The modified sodium iron pyrophosphate prepared in this embodiment includes a Na4Fe3(PO4)2P2O7 core and a coating layer coated on the surface thereof, wherein the coating layer includes sodium phosphate and Na2C2O4, and the Na4Fe3(PO4)2P2O7 core contains defects of Na and Fe, forming Fe 3+ and Fe 2+ of mixed valence.
[0055] Example 3
[0056] This embodiment provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0057] (1) Na4Fe3(PO4)2P2O7, Na2C2O4 and phosphoric acid were mixed by dry stirring at a molar ratio of 1:0.04:0.02 to obtain a mixture with a particle size of 8 μm;
[0058] (2) The mixture obtained in step (1) is sintered at 750° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0059] In this embodiment, the molar ratio of the sodium supplement Na2C2O4 to Na4Fe3(PO4)2P2O7 is a=0.04, and the molar ratio of the phosphorus source to Na4Fe3(PO4)2P2O7 is b=0.02, then c=(10a) 2 / (2.25b)=3.56.
[0060] The modified sodium iron pyrophosphate prepared in this embodiment includes a Na4Fe3(PO4)2P2O7 core and a coating layer coated on the surface thereof, wherein the coating layer includes sodium phosphate and Na2C2O4, and the Na4Fe3(PO4)2P2O7 core contains defects of Na and Fe, forming Fe 3+ and Fe 2+ of mixed valence.
[0061] Comparative Example 1
[0062] This comparative example provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0063] (1) Na4Fe3(PO4)2P2O7, Na2C2O4 and phosphoric acid were uniformly mixed by dry stirring in a molar ratio of 1:0.035:0.04 to obtain a mixture with a particle size of 8 μm;
[0064] (2) The mixture obtained in step (1) is sintered at 750° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0065] In this comparative example, the molar ratio of the sodium supplement Na2C2O4 to Na4Fe3(PO4)2P2O7 is a=0.035, and the molar ratio of the phosphorus source to Na4Fe3(PO4)2P2O7 is b=0.04, then c=(10a) 2 / (2.25b)=1.36.
[0066] The modified sodium iron pyrophosphate prepared in this comparative example includes a Na4Fe3(PO4)2P2O7 core and a coating layer coated on the surface thereof, wherein the coating layer includes sodium phosphate and Na2C2O4, and the Na4Fe3(PO4)2P2O7 core contains defects of Na and Fe, forming Fe 3+ and Fe 2+ of mixed valence.
[0067] Comparative Example 2
[0068] This comparative example provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0069] (1) Na4Fe3(PO4)2P2O7, Na2C2O4 and phosphoric acid were mixed by dry stirring at a molar ratio of 1:0.015:0.01 to obtain a mixture with a particle size of 8 μm;
[0070] (2) The mixture obtained in step (1) is sintered at 750° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0071] In this comparative example, the molar ratio of the sodium supplement Na2C2O4 to Na4Fe3(PO4)2P2O7 is a=0.015, and the molar ratio of the phosphorus source to Na4Fe3(PO4)2P2O7 is b=0.01, then c=(10a) 2 / (2.25b)=1.
[0072] The modified sodium iron pyrophosphate prepared in this comparative example includes a Na4Fe3(PO4)2P2O7 core and a coating layer coated on the surface thereof, wherein the coating layer includes sodium phosphate and Na2C2O4, and the Na4Fe3(PO4)2P2O7 core contains defects of Na and Fe, forming Fe 3+ and Fe 2+ of mixed valence.
[0073] Comparative Example 3
[0074] This comparative example provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0075] (1) Na4Fe3(PO4)2P2O7, Na2C2O4 and phosphoric acid were uniformly mixed by dry stirring in a molar ratio of 1:0.06:0.035 to obtain a mixture with a particle size of 8 μm;
[0076] (2) The mixture obtained in step (1) is sintered at 750° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0077] In this comparative example, the molar ratio of the sodium supplement Na2C2O4 to Na4Fe3(PO4)2P2O7 is a=0.06, and the molar ratio of the phosphorus source to Na4Fe3(PO4)2P2O7 is b=0.035, then c=(10a) 2 / (2.25b)=4.57.
[0078] The modified sodium iron pyrophosphate prepared in this comparative example includes a Na4Fe3(PO4)2P2O7 core and a coating layer coated on the surface thereof, wherein the coating layer includes sodium phosphate and Na2C2O4, and the Na4Fe3(PO4)2P2O7 core contains defects of Na and Fe, forming Fe 3+ and Fe 2+ of mixed valence.
[0079] Comparative Example 4
[0080] This comparative example provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0081] (1) Na4Fe3(PO4)2P2O7, sodium nickelate and phosphoric acid were mixed by dry stirring at a molar ratio of 1:0.035:0.02 to obtain a mixture with a particle size of 8 μm;
[0082] (2) The mixture obtained in step (1) is sintered at 750° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0083] In this comparative example, the molar ratio of the sodium supplement sodium nickelate to Na4Fe3(PO4)2P2O7 is a=0.035, and the molar ratio of the phosphorus source to Na4Fe3(PO4)2P2O7 is b=0.02, then c=(10a) 2 / (2.25b)=2.72.
[0084] The modified sodium iron pyrophosphate prepared in this comparative example includes a Na4Fe3(PO4)2P2O7 core and a coating layer coated on the surface thereof, wherein the coating layer includes sodium phosphate and sodium nickelate, and the Na4Fe3(PO4)2P2O7 core contains defects of Na and Fe, forming Fe 3+and Fe 2+ of mixed valence.
[0085] Comparative Example 5
[0086] This comparative example provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0087] (1) Na4Fe3(PO4)2P2O7, Na2C2O4 and phosphoric acid were mixed by dry stirring at a molar ratio of 1:0.035:0.02 to obtain a mixture with a particle size of 8 μm;
[0088] (2) The mixture obtained in step (1) is sintered at 650° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0089] In this comparative example, the molar ratio of the sodium supplement Na2C2O4 to Na4Fe3(PO4)2P2O7 is a=0.035, and the molar ratio of the phosphorus source to Na4Fe3(PO4)2P2O7 is b=0.02, then c=(10a) 2 / (2.25b)=2.72.
[0090] The modified sodium iron pyrophosphate prepared in this comparative example includes a Na4Fe3(PO4)2P2O7 core and a coating layer coated on the surface thereof, wherein the coating layer includes sodium phosphate and Na2C2O4, and the Na4Fe3(PO4)2P2O7 core contains defects of Na and Fe, forming Fe 3+ and Fe 2+ of mixed valence.
[0091] Comparative Example 6
[0092] This comparative example provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0093] (1) Na4Fe3(PO4)2P2O7, Na2C2O4 and phosphoric acid were mixed by dry stirring at a molar ratio of 1:0.035:0.02 to obtain a mixture with a particle size of 8 μm;
[0094] (2) The mixture obtained in step (1) is sintered at 850° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0095] In this comparative example, the molar ratio of the sodium supplement Na2C2O4 to Na4Fe3(PO4)2P2O7 is a=0.035, and the molar ratio of the phosphorus source to Na4Fe3(PO4)2P2O7 is b=0.02, then c=(10a) 2 / (2.25b)=2.72.
[0096] The modified sodium iron pyrophosphate prepared in this comparative example includes a Na4Fe3(PO4)2P2O7 core and a coating layer coated on the surface thereof, wherein the coating layer includes sodium phosphate and Na2C2O4, and the Na4Fe3(PO4)2P2O7 core contains defects of Na and Fe, forming Fe 3+ and Fe 2+ of mixed valence.
[0097] Comparative Example 7
[0098] This comparative example provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0099] (1) Na4Fe3(PO4)2P2O7 and Na2C2O4 were mixed by dry stirring at a molar ratio of 1:0.035 to obtain a mixture with a particle size of 8 μm;
[0100] (2) The mixture obtained in step (1) is sintered at 750° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0101] Comparative Example 8
[0102] This comparative example provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0103] (1) Na4Fe3(PO4)2P2O7 and phosphoric acid were mixed by dry stirring at a molar ratio of 1:0.02 to obtain a mixture with a particle size of 8 μm;
[0104] (2) The mixture obtained in step (1) is sintered at 750° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0105] Comparative Example 9
[0106] This comparative example provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0107] (1) Na4Fe3(PO4)2P2O7, Na2C2O4 and phosphoric acid were mixed by dry stirring at a molar ratio of 1:0.035:0.078 to obtain a mixture with a particle size of 8 μm;
[0108] (2) The mixture obtained in step (1) is sintered at 750° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0109] In this comparative example, the molar ratio of the sodium supplement Na2C2O4 to Na4Fe3(PO4)2P2O7 is a=0.035, and the molar ratio of the phosphorus source to Na4Fe3(PO4)2P2O7 is b=0.078, then c=(10a) 2 / (2.25b)=0.7.
[0110] Comparative Example 10
[0111] This comparative example provides a method for preparing modified sodium ferric pyrophosphate, comprising the following steps:
[0112] (1) Na4Fe3(PO4)2P2O7, Na2C2O4 and phosphoric acid were mixed by dry stirring at a molar ratio of 1:0.05:0.02 to obtain a mixture with a particle size of 8 μm;
[0113] (2) The mixture obtained in step (1) is sintered at 750° C. for 10 h in a nitrogen atmosphere, and then the sintered product is ground to a D50 particle size of 6 μm to obtain modified sodium ferric pyrophosphate.
[0114] In this comparative example, the molar ratio of the sodium supplement Na2C2O4 to Na4Fe3(PO4)2P2O7 is a=0.05, and the molar ratio of the phosphorus source to Na4Fe3(PO4)2P2O7 is b=0.02, then c=(10a) 2 / (2.25b)=5.5.
[0115] The modified sodium iron pyrophosphate prepared in the above embodiments and comparative examples and the unmodified Na4Fe3(PO4)2P2O7 were used as positive electrode active materials for sodium ion batteries. The positive electrode active material, carbon black conductive agent and binder polyvinylidene fluoride (PVDF) were added to N-methyl-2-pyrrolidone (NMP) in a mass ratio of 90:5:5 and mixed evenly to prepare a positive electrode slurry with a solid content of 45%. Subsequently, each positive electrode slurry was coated on an aluminum foil with a thickness of 10-15 μm, and a positive electrode sheet was made after vacuum drying and rolling. A sodium metal sheet was used as the negative electrode, and the electrolyte ratio was 1.15MNaPF6, EC:DMC (1:1 vol%) to assemble a button battery, and its electrochemical performance was tested.
[0116] The button cell was tested at 25°C using a Blue Electric battery testing system with a test voltage range of 1.5 to 3.6V. The charge and discharge capacity of the battery at 0.1C, the discharge capacity at 1C, and the discharge capacity / charge capacity ratio when the battery was charged at 0.1C and discharged at 1C were tested. The battery was cycled at 1C for 200 weeks, and the 200-week cycle retention rate was obtained by dividing the 200th week discharge capacity by the first week discharge capacity. The test results are shown in Table 1.
[0117] Table 1
[0118]
[0119]
[0120] By comparing Example 1 with Comparative Example 1, it can be seen that only when the molar ratio of phosphoric acid to Na4Fe3(PO4)2P2O7 is within an appropriate range can the cyclic stability of the obtained product, modified sodium iron pyrophosphate, be better. However, the phosphoric acid content in Comparative Example 1 is too high, resulting in poor stability of the obtained material.
[0121] By comparing Examples 1-3 with Comparative Examples 2-3, it can be seen that only when the molar ratio of the sodium supplement Na2C2O4 and Na4Fe3(PO4)2P2O7 is in the range of 0.015<a<0.06, the rate and cycle stability of the prepared modified sodium iron phosphate can be better. The sodium supplement content in Comparative Example 2 is relatively low, which will affect the discharge capacity and cycle stability of the material. The sodium supplement content in Comparative Example 3 is relatively high, which will also affect the rate and cycle stability of the material.
[0122] By comparing Example 1 with Comparative Example 4, it can be seen that the use of the preferred sodium supplementer of the present invention can better exert its synergistic effect with phosphoric acid, thereby improving the diffusion efficiency of sodium ions, solving the problem of capacity decay, and will not affect the performance of Na4Fe3(PO4)2P2O7 itself; while in Comparative Example 4, sodium nickelate is used as the sodium supplementer, which will introduce nickel elements into the modified Na4Fe3(PO4)2P2O7, thereby reducing the conductivity of the material, and thus the 50-week cycle capacity retention rate of the obtained material decreases.
[0123] By comparing Example 1 with Comparative Examples 5-6, it can be seen that calcining Na4Fe3(PO4)2P2O7 with phosphoric acid (phosphorus source) and sodium oxalate (sodium supplement) at 700-800°C is more conducive to the reaction of phosphoric acid and sodium oxalate to form a sodium phosphate coating layer, and also enables the phosphorus source to modify Na4Fe3(PO4)2P2O7 to adjust the mixed valence state of Fe, thereby improving the rate performance and cycle performance of the material; while the sintering temperature in Comparative Example 5 is too low, which will affect the cycle stability of the material, and the sintering temperature in Comparative Example 6 is too high, which will affect the rate performance of the material.
[0124] By comparing Example 1 with Comparative Examples 7-8 and Na4Fe3(PO4)2P2O7 without any modification, it can be seen that the phosphorus source and the sodium supplement are indispensable, and the two are synergistically improved in a suitable ratio to improve the electronic conductivity and ion diffusion capacity of the material. However, the above comparative examples lack at least one of the phosphorus source and the sodium supplement, and the synergistic effect of coating modification and sodium supplementation cannot be achieved, and thus the improvement of electronic conductivity and ion diffusion capacity cannot be achieved at the same time. Therefore, the discharge capacity, 50-week cycle retention rate and 1C / 0.1C capacity ratio of the materials prepared in the above comparative examples at different rates are significantly worse than those in Example 1.
[0125] By comparing Example 1 with Comparative Examples 9-10, it can be seen that only when the contents of Na4Fe3(PO4)2P2O74, sodium supplement and phosphorus source meet 1<(10a) 2 / (2.25b)<5.33, the synergistic effect of the phosphorus source and the sodium supplement can be fully exerted, the mixed valence of Na4Fe3(PO4)2P2O7 can be adjusted, and a coating layer of the sodium supplement and sodium phosphate can be formed on the surface of Na4Fe3(PO4)2P2O7, taking into account the coating modification and sodium supplement effects, so that the prepared modified Na4Fe3(PO4)2P2O7 has higher specific capacity, rate performance and cycle performance. However, the c value in comparative example 9 is low, lower than 1, which will lead to deviation in cycle stability; the c value in comparative example 10 is high, higher than 5.33, which will lead to poor rate and cycle stability.
[0126] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0127] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A modified sodium ferric pyrophosphate, characterized in that: It includes a core and a coating layer coated on the surface of the core; wherein the core is Na4Fe3(PO4)2P2O7, and the coating layer includes a sodium supplement and a reaction product generated by a high-temperature reaction of the sodium supplement and a phosphorus source.
2. The modified sodium ferric pyrophosphate according to claim 1, characterized in that The molar ratio of the sodium supplement to the Na4Fe3(PO4)2P2O7 is denoted as a, and the molar ratio of the phosphorus source to the Na4Fe3(PO4)2P2O7 is denoted as b, then 1<c=(10a) 2 / (2.25b)<5.33, and 0.015<a<0.06, 0.01<b<0.
03.
3. The modified sodium ferric pyrophosphate according to claim 1, characterized in that The sodium supplement is sodium oxalate.
4. The modified sodium ferric pyrophosphate according to claim 1, characterized in that The phosphorus source includes at least one of phosphoric acid, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.
5. A method for preparing modified sodium ferric pyrophosphate according to any one of claims 1 to 4, characterized in that: The steps include: (1) mixing Na4Fe3(PO4)2P2O7, a sodium supplement and a phosphorus source to obtain a mixture; (2) The mixture is sintered at high temperature, and then ground to obtain the modified sodium ferric pyrophosphate.
6. The method for preparing modified sodium ferric pyrophosphate according to claim 5, characterized in that: In the step (1), the particle size of the mixture is 2 to 15 μm.
7. The method for preparing modified sodium ferric pyrophosphate according to claim 5, characterized in that: In the step (2), the high temperature sintering is performed under the protection of an inert gas, and the inert gas includes at least one of nitrogen and argon; And / or, the sintering temperature of the high temperature sintering is 700-800° C., and the sintering time is 9-12 hours.
8. The method for preparing modified sodium ferric pyrophosphate according to claim 5, characterized in that: In the step (2), the modified sodium ferric pyrophosphate obtained after grinding has a D50 particle size of 0.5 to 8 μm.
9. Use of the modified sodium ferric pyrophosphate according to any one of claims 1 to 4 or the modified sodium ferric pyrophosphate obtained by the preparation method according to any one of claims 5 to 8 in a sodium ion battery, characterized in that: The modified sodium iron pyrophosphate is used as the positive electrode active material of the sodium ion battery.
10. The use according to claim 9, characterized in that: The sodium ion battery further comprises a negative electrode and an electrolyte; the negative electrode is a sodium metal sheet, and the electrolyte comprises sodium hexafluorophosphate, ethylene carbonate and dimethyl carbonate.
Citation Information
Patent Citations
Nanometer sodium oxalate composite positive electrode active material and application thereof
CN115954445A
Sodium supplement additive and carbon co-coated composite sodium ferric phosphate positive electrode material and preparation method thereof
CN116845214A
Sodium ferric phosphate pyrophosphate carbon composite positive electrode material as well as preparation method and application thereof
CN117374257A
Sodium supplement slurry and preparation method thereof, positive plate and sodium ion battery
CN117936788A
Sodium supplementing agent, positive plate and sodium ion battery
CN118213535A